2015
DOI: 10.3390/ijms16011691
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Αpplications of Ιnterleukins in Cancer Immunotherapy

Abstract: Over the past years, advances in cancer immunotherapy have resulted in innovative and novel approaches in molecular cancer diagnostics and cancer therapeutic procedures. However, due to tumor heterogeneity and inter-tumoral discrepancy in tumor immunity, the clinical benefits are quite restricted. The goal of this review is to evaluate the major cytokines-interleukins involved in cancer immunotherapy and project their basic biochemical and clinical applications. Emphasis will be given to new cytokines in pre-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 87 publications
0
45
0
3
Order By: Relevance
“…IL-6 plays a crucial role in tumor microenvironment regulation in a number of cancers, including breast, oral, prostate, and pancreatic cancers [26,27,28,29,30,31,32]. Higher levels of IL-6 in the blood of patients have been associated with advanced/metastatic cancers [26,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 plays a crucial role in tumor microenvironment regulation in a number of cancers, including breast, oral, prostate, and pancreatic cancers [26,27,28,29,30,31,32]. Higher levels of IL-6 in the blood of patients have been associated with advanced/metastatic cancers [26,33,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a deep understanding of factors regulating IL-6 expression might be relevant for the development of novel therapeutic approaches targeting its activity [28, 29]. We have previously reported that IL-6 is induced in prostate cancer cells and that the ETS factor ESE1 was an important mediator enhancing the NFKb response [30].…”
Section: Discussionmentioning
confidence: 99%
“…For many years, researchers have been searching for anticancer agents from the human body, since peptides from humans display little immunogenicity. Several peptides from human sources have been successfully used clinically for treatment of human cancer, such as interferons and interleukins (22)(23)(24). However, these kinds of peptides usually do not inhibit cancer cell growth directly; they affect the growth of tumors via an immune effect.…”
Section: Discussionmentioning
confidence: 99%